2015
DOI: 10.1007/s13280-014-0616-6
|View full text |Cite
|
Sign up to set email alerts
|

Plant uptake of phosphorus and nitrogen recycled from synthetic source-separated urine

Abstract: Urine contains about 50 % of the phosphorus (P) and about 90 % of the nitrogen (N) excreted by humans and is therefore an interesting substrate for nutrient recovery. Source-separated urine can be used to precipitate struvite or, through a newly developed technology, nitrified urine fertilizer (NUF). In this study, we prepared 33P radioisotope- and stable 15N isotope-labeled synthetic NUF (SNUF) and struvite using synthetic urine and determined P and N uptake by greenhouse-grown ryegrass (Lolium multiflorum va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
72
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(80 citation statements)
references
References 32 publications
(57 reference statements)
2
72
2
1
Order By: Relevance
“…Struv was the least efficient of the three reject water products, with a P uptake less than half that in the Prec treatment and an RFE of just 46%. This is in contrast to many previous studies that found a better or similar P fertilizer value of struvite compared to TSP or other water‐soluble P sources ( Cabeza et al, ; Achat et al, ; Bonvin et al, ; Vogel et al., ; Kahiluoto et al, ). Furthermore, the low pH level during incubation (Tab.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Struv was the least efficient of the three reject water products, with a P uptake less than half that in the Prec treatment and an RFE of just 46%. This is in contrast to many previous studies that found a better or similar P fertilizer value of struvite compared to TSP or other water‐soluble P sources ( Cabeza et al, ; Achat et al, ; Bonvin et al, ; Vogel et al., ; Kahiluoto et al, ). Furthermore, the low pH level during incubation (Tab.…”
Section: Discussioncontrasting
confidence: 99%
“…3) could have been expected to promote fast dissolution of struvite P (Vogel et al, 2017), but also in the incubation experiment, there was a surprisingly low effect of struvite. Likely explanations for the low struvite efficiency seen in the present study, is the relatively short growth period (6 weeks)/incubation time (3 weeks), combined with the fact that whole struvite granules (1-2 mm) were used instead of the pulverized material (see discussion below) as in Cabeza et al (2011), Achat et al (2014), and Bonvin et al (2015. This explanation is supported by the findings of Talboys et al (2016), who identified a low efficiency of struvite after 30 d growth of spring wheat (just 30% relative to di-ammonium phosphate), whereas after 90 d growth, the P recovery from struvite was not significantly different from TSP.…”
Section: Discussionmentioning
confidence: 81%
“…The failed P cycle in mining, fertilizer production, and land application of P in livestock manure, food waste, and human waste is the underlying problem since it limits sustainable P use. Contributing to a solution is the need to Realign the inputs of P, Reuse P from manures and residuals (Bonvin et al, 2015;Stutter, 2015), Recover P from waste, Redefine systems, and Reduce P losses. This was defined as the 5R's of P management stewardship by Schoumans et al, (2015), which is an update of the "4R" nutrient management stewardship, specifically formulated to address the failed P cycle, which is the root cause of P related use-impairments of water from accelerated eutrophication.…”
Section: Future Challenges For Fertilizer Management and Water Qualitymentioning
confidence: 99%
“…De plus, l'engrais en question est pasteurisé pendant la distillation, ce qui permet de détruire tous les virus qui auraient survécu à la nitrification. Gonidanga et al (2004) (Bonvin et al, 2015). Cet engrais liquide contient toutes les substances nécessaires à la croissance végétale : de l'azote, du phosphore et du potassium mais aussi des oligoéléments tels que le fer, le zinc et le bore qui contribuent fortement au bon développement des végétaux.…”
unclassified